2013
DOI: 10.1128/iai.00405-13
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in the Promoter of the Gene Encoding the Mga Regulator Alters Host-Pathogen Interactions in Group A Streptococcus Carrier Strains

Abstract: cHumans commonly carry pathogenic bacteria asymptomatically, but the molecular factors underlying microbial asymptomatic carriage are poorly understood. We previously reported that two epidemiologically unassociated serotype M3 group A Streptococcus (GAS) carrier strains had an identical 12-bp deletion in the promoter of the gene encoding Mga, a global positive gene regulator. Herein, we report on studies designed to test the hypothesis that the identified 12-bp deletion in the mga promoter alters GAS virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 63 publications
1
40
2
2
Order By: Relevance
“…We previously showed that peak sclA transcript coincides with peak mga transcript levels in serotype M3 GAS (15). Thus, we hypothesized that sclA transcript would be produced in a strain with either sclA Invasive or sclA Carrier .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that peak sclA transcript coincides with peak mga transcript levels in serotype M3 GAS (15). Thus, we hypothesized that sclA transcript would be produced in a strain with either sclA Invasive or sclA Carrier .…”
Section: Resultsmentioning
confidence: 99%
“…The transcript levels of sclA were assayed as previously described (15). Briefly, RNA was isolated and purified by using an RNeasy kit according to the manufacturer's instructions (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Если Fc-рецепторные белки для нативного IgG были описаны ранее [14,15], то на сегодня наука не располагает сведениями о белках, связыва-ющих IC. Недавно было показано [6], что штаммы СГА, выделяемые от асимптомных носителей инфекции, нередко несут делецию в промо-торной области гена Mga-регулятора. Есте-ственно, что такие штаммы-мутанты долж-ны быть дефектными по М-белкам, и в силу этого лишены способности связывать IC.…”
Section: заключениеunclassified